2006
DOI: 10.1038/sj.onc.1209262
|View full text |Cite
|
Sign up to set email alerts
|

Lactate dehydrogenase-B is silenced by promoter hypermethylation in human prostate cancer

Abstract: In order to identify novel candidates associated with prostate cancer metastasis, we compared the proteomic profile of the poorly metastatic human prostate cancer cell line LNCaP, with its highly metastatic variant LNCaP-LN3, by two-dimensional gel electrophoresis. A major protein spot (pI of 5.9 and molecular weight of 37 kDa) was seen in LNCaP cells, but not in LNCaP-LN3 cells and was identified as lactate dehydrogenase-B (LDHB), by tandem mass spectrometry. Furthermore, enzyme kinetic assays and zymography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
90
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(99 citation statements)
references
References 44 publications
(42 reference statements)
6
90
1
Order By: Relevance
“…While an essential function of LDHA in tumor metabolism has been described (40), the role of LDHB is less clear. One report has shown that the mTOR pathway controls LDHB expression, whereas another report has shown that LDHB transcription is shut off by promoter methylation in bladder, colon, and prostate cancers (41)(42)(43)(44). In the context of lung adenocarcinoma, we observed that LDHB is upregulated in KRAS aberrant tumors and in a subset of cell lines containing other oncogenic drivers.…”
Section: Discussionmentioning
confidence: 48%
“…While an essential function of LDHA in tumor metabolism has been described (40), the role of LDHB is less clear. One report has shown that the mTOR pathway controls LDHB expression, whereas another report has shown that LDHB transcription is shut off by promoter methylation in bladder, colon, and prostate cancers (41)(42)(43)(44). In the context of lung adenocarcinoma, we observed that LDHB is upregulated in KRAS aberrant tumors and in a subset of cell lines containing other oncogenic drivers.…”
Section: Discussionmentioning
confidence: 48%
“…It is known that the majority of LDH subunits detected in the serum is LDH-B, although LDH-A exists in a lesser amount (Maekawa, 1988). The absence of LDH-B expression and its enzyme activities have been reported in cell lines of breast , prostate (Leiblich et al, 2006), gastric and pancreatic cancer (Maekawa et al, 2003), suggested to be driven by promoter hypermethylation. As LDH-B kinetically favours the backward reaction of pyruvatelactate conversion (Augoff et al, 2014), this may suggest that LDH-A, which mostly catalyses the formation of lactate, is more relevant to cancer than LDH-B (Maekawa, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…This relationship allows the tumor to take up lactate and to convert it to pyruvate, which is processed in the tricarboxylic acid cycle. However, opposing this model, prostate tumors overexpress lactate dehydrogenase A [129,[131][132][133], which preferentially works in the direction of lactate production [33,34]. Consistently, lactate dehydrogenase B, which catalyzes the lactate to pyruvate conversion, is suppressed [131,134].…”
Section: Early Stage Prostate Cancer Metabolismmentioning
confidence: 99%
“…However, opposing this model, prostate tumors overexpress lactate dehydrogenase A [129,[131][132][133], which preferentially works in the direction of lactate production [33,34]. Consistently, lactate dehydrogenase B, which catalyzes the lactate to pyruvate conversion, is suppressed [131,134]. This is further functionally supported by experiments with hyperpolarized pyruvate, where in situ tumors convert pyruvate into lactate [135][136][137].…”
Section: Early Stage Prostate Cancer Metabolismmentioning
confidence: 99%